Regime de memória romano: imagens do herói Héracles nos escritos de Luciano de Samósata (século II d.C.) - ARANTES JÚNIOR, Edson (2008)
Based on literature and on the analysis of texts by Lucian of Samosata, who was a Syrian author from the second century of the Christian era, the present essay aims to pose a few questions about a very influent historiographic construct: the idealization of the antonine era. To elucidate the problem, we have elaborated the concept of memory regime, which seeks to encompass the metanarrative limits that are necessary for the construction of the discourses. For such, we debated the ways in which the elite of the Roman Empire built an imperial culture, based on dialogue with the dominated cultures hence this paper debates the notion of Romanization. We have also pointed out the ways in which the discourses are validated by historical agents and some processes that involved the art of memory, a knowledge deeply rooted in the heart of roman aristocracy. We blended similar theoretical constructions with one clear example: the myth of Heracles and its diverse representations in Lucian of Samosata s writings, a mythical element whose analysis is fundamental, since the imperial propaganda of the antonine era is permeated with it. Therefore, this paper strives to show how this golden era of roman history presents conflicts even if they are in the form of representation